Efeitos do tipo de rizoma de multiplicação e da cobertura morta no desenvolvimento e produtividade de cúrcuma (Curcuma longa L.) - Menezes, A.; Borella, J. C.; França, S. C.; Masca, M. G C C [UNESP] (My University, 2005)
The aim of this study was to evaluate the influence of different types of rhizomes utilized as seed and the effects of mulch in the culture of Turmeric. This work was conducted in the experimental cultivation area of the Universidade de Ribeirão Preto - UNAERP, in Ribeirao Preto, state of Sao Paulo, Brazil from September/1997 to July/1998. The experiments were arranged in a randomized complete block with a factorial arrangement 2x3, design with 4 replications (32 plants each). The treatments consisted of the use of types of rhizomes utilized to proliferation (head and finger) and types of mulch (absent, grass and leaves/branches). This study investigated proliferation (61, 88 and 124 days after installation), length, shooting and number of leaves of the mother plant besides the number of leaves of the shoot (112, 146 and 233 days after installation), number of finger rhizomes and head rhizomes, fresh and dry biomass of rhizomes and the yield of essential oil (after harvest - July 1998). Obtained results showed a great influence of the type of rhizome used to proliferation. Head rhizomes produced, in weight, about 30% more, when compared to plants from finger rhizomes. Mulching almost duplicated rhizome productivity from 2338 kg.ha -1 of dry rhizomes to 4499 kg.ha -1, when rhizome used to proliferation was finger and from 3046 kg.ha -1 to 5943 kg.ha -1, when using head rhizomes. The yield of essential oil did not show any alteration, independently of the treatments realized.
Effects of type of rhizome used to proliferation and mulching on growth and productivity of turmeric (Curcuma longa L.)
Keywords: Curcuma longa L.; Essential oil; Medicinal plants; Mulch; Rhizome; essential oil; biomass production; Brazil; cultivated species; Curcuma longa; medicinal plant; mulch; nonhuman; plant growth; plant seed; rhizome; shoot growth